IPR, Biosafety and Bioethics - Deepa Goel (Pearson, 2013)
This book provides a broad coverage of three areas ofpatentingintellectual property rights (IPR), biosafety andbioethics. It creates awareness about the value of IPR in ourlives. The book also fosters a better understanding of the rightsassociated with IPR such as copyright, patent, trademarks,industrial designs, geographical indications and so on. Biosafetyand bioethical issues prevalent in modern society are discussed.The text covers the complete syllabi of all major Indianuniversities and caters to the needs of Indian students.